Loss of Spike N370 glycosylation as an important evolutionary event for the enhanced infectivity of SARS-CoV-2 - Zhang, Shuyuan; Liang, Qingtai; He, Xinheng; Zhao, Chongchong; Ren, Wenlin; Yang, Ziqing; Wang, Ziyi; Ding, Qiang; Deng, Haiteng; Wang, Tong; Zhang, Linqi; Wang, Xinquan (Cell Research, 2022)
SARS-CoV-2 belongs to the Sarbecovirus subgenus of betacoronaviruses and other members in this subgenus include SARS-CoV and coronaviruses mainly found in bats1. It is generally believed that like SARS-CoV and MERS-CoV, SARS-CoV-2 has a natural origin and was selected either in animal hosts before zoonotic transfer, or in humans following zoonotic transfer2. However, the molecular determinants for host expansion of SARS-CoV-2 from animal reservoirs to humans remain largely unclear. The Spike (S) glycoprotein of coronaviruses mediates viral entry by binding host receptor and fusing viral and cellular membranes3. SARS-CoV-2 S glycoprotein contains 22 N-glycosylation sites and 17 O-glycosylation sites4. Cryo-EM structures of the bat RaTG13 and pangolin PCoV_GX coronavirus S trimers showed that, besides protein–protein interactions, one RBD is also contacted by N-glycans linked to three asparagine residues of the neighboring S protomer (N165 and N234 in the NTD and N370 in the RBD) (Supplementary information, Fig. S1a)5. However, the N370 glycosylation is lost in the SARS-CoV-2 S glycoprotein due to the threonine-to-alanine mutation at position 372 (Supplementary information, Fig. S1a). In contrast, the typical -NST- glycosylation motif is highly conserved among eight SARS-CoV-2-related Sarbecovirus members including SARS-CoV and coronaviruses from bat and pangolin (Supplementary information, Fig. S1b).